Multilingual Lifeworlds and Textual Monolingualism: Pseudotranslation in Katerina Poladjan, Olga Grjasnowa, and Nino Haratischwili - Marie-Christine Boucher (Studies in 20th & 21st Century Literature, 2024)
A great deal of existing research on literary multilingualism focuses on the explicit presence of multiple languages in literary works. Yet these texts represent only a relatively marginal portion of contemporary literary production. To focus on this rare literary phenomenon neglects the fact that literary systems pressure most authors to write increasingly monolingual texts—which does not preclude them from portraying scenes of everyday multilingual life. Rather than rendering different languages directly in the text, however, this multilingualism is often excluded: in a monolingual (literary) world, authors translate worldly multilingualism into textual monolingualism. I analyze the distinct strategies authors employ in this type of translation in three German-language novels partly set in the Caucasus region: Das achte Leben (Für Brilka) (Nino Haratischwili, 2014), Die juristische Unschärfe einer Ehe (Olga Grjasnowa, 2014), and Hier sind Löwen (Katerina Poladjan, 2019). Using pseudotranslation as a mode of reading (Rath 2017), I probe the presence of multilingualism forced into absence.
Keywords: textual monolingualism; pseudotranslation; German literature; Katerina Poladjan; Olga Grjasnowa; Nino Haratischwili